Designing the landscape for technological development in neonatal neurocritical care. Issue 4 (29th August 2018) - Hamilton, Colin; Phaal, Robert; Brahmbhatt, Mita; Jarritt, Peter; Austin, Topun
Abstract : Objectives: To identify current 'gaps' in clinical practice or therapeutic knowledge of the care of neonatal neurointensive care patients and to determine the impact healthcare technologies can have on improving outcomes. Design: The Cambridge Institute for Manufacturing's (IfM) roadmapping methodology. Setting: Cambridge, UK. Participants: 16 delegates were selected through professional networks. They provided coverage of academia and clinical skills, as well as expertise in neonatology, engineering and technology development. Main outcome measures: A 'strategic landscape' has been developed with 'landmarks' identified as 'trends or drivers', 'patient pathway experience and unmet needs' and 'enabling project or resources'. Priorities were voted on by delegates. Results: 26 strategic 'landmarks' were identified, and of these 8 were considered 'trends or drivers', 8 'patient pathway experience and unmet needs' and 10 as 'enabling project or resources'. Of these, five priorities for the future of neonatal neurocritical care were identified by a voting process: real-time video monitoring for parents; individualised management of preterm infants in neonatal neurocritical care based on real-time multimodal monitoring; continuous electroencephalogram monitoring for early seizure diagnosis; neuroprotection: understanding basic mechanisms; and sleep measurement. Conclusions: Through the use of the IfM methodology, a list of priorities has been developed for future work into improving the experience and possible outcomes of newborn infants with brain injuries and their families. While not an exhaustive list, it provides the beginning for a national conversation on the topic.